Non-Performing Loans Indonesian Banking Industry: Before and During Covid-19 Pandemic - Muhammad Nur Hakim; Ariodillah Hidayat; Imam Asngari; Xenaneira Shodrokova (Economics Development Analysis Journal, 2023)
This study examines the factors influencing Non-Performing Loans in the Indonesian Banking Industry, specifically the Bank Group based on Core Capital (KBMI) 4, both before and during the COVID-19 Pandemic. Secondary data, spanning from January 2019 to September 2021, is utilized in this analysis. The study employs the error correction (ECM) model through regression analysis techniques. The findings indicate that the Loan Deposit Ratio and Bank Indonesia (BI) Rate significantly and negatively impact Non-Performing Loans in both the short and long term. Furthermore, the Dummy COVID-19 variable significantly and positively influences Non-Performing Loans in both the short and long term. While Net Interest Margin exhibits a positive but non-significant effect in the short term, it demonstrates a positive and significant effect on Non-Performing Loans in the long term.